2008
DOI: 10.1002/jbm.a.32029
|View full text |Cite
|
Sign up to set email alerts
|

Directional conductivity in SWNT‐collagen‐fibrin composite biomaterials through strain‐induced matrix alignment

Abstract: Composite biomaterials incorporating fibroblast cells, collagen Type I, fibrin, and 2 wt % carboxylated SWNT were created, and their properties were compared with similar control constructs without SWNT. Alignment of the matrix was stimulated by application of 8% cyclic strain for three 12-h periods over three days. All constructs underwent cell-mediated gel compaction to 15-20% of their initial volume, which was not affected by SWNT loading. Mechanical strain increased the rate of compaction, and strained con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 36 publications
5
54
1
Order By: Relevance
“…Because flow and strain are necessarily coupled, we could not differentiate specific responses to flow versus strain, but this alignment was consistent with our previous studies showing that fibroblasts in collagen gels undergoing interstitial flow alone (without matrix compression) align perpendicular to the direction of flow Swartz, 2003, 2006). We note that most of the previous work on fibroblast mechanobiology has been done by applying either tension or confined compression to the cells (Eastwood et al, 1998;Grinnell, 2003;Liu et al, 1999b;Wang et al, 2007), with tensional forces driving alignment of cells parallel to the strain direction (Henshaw et al, 2006;Voge et al, 2008); this is consistent with our findings. This demonstrates the usefulness of this model system for mechanobiology involving 3D dynamic compressive or tensile stresses.…”
Section: Dynamic Strain Application To Fibroblastssupporting
confidence: 91%
“…Because flow and strain are necessarily coupled, we could not differentiate specific responses to flow versus strain, but this alignment was consistent with our previous studies showing that fibroblasts in collagen gels undergoing interstitial flow alone (without matrix compression) align perpendicular to the direction of flow Swartz, 2003, 2006). We note that most of the previous work on fibroblast mechanobiology has been done by applying either tension or confined compression to the cells (Eastwood et al, 1998;Grinnell, 2003;Liu et al, 1999b;Wang et al, 2007), with tensional forces driving alignment of cells parallel to the strain direction (Henshaw et al, 2006;Voge et al, 2008); this is consistent with our findings. This demonstrates the usefulness of this model system for mechanobiology involving 3D dynamic compressive or tensile stresses.…”
Section: Dynamic Strain Application To Fibroblastssupporting
confidence: 91%
“…Since many tissues, e.g., striated muscle, 6 cartilage, 7 or cornea 8 , to name just a few examples, have anisotropic hierarchical morphologies, there is a growing interest in developing approaches for the fabrication of anisotropic hydrogels that exhibit direction-dependent pore shape, microstructure, stiffness, and conductivity. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In tissue engineering, aside from biomimicry, anisotropic pore shape and hydrogel structure, in general, are important for cell guidance 22 and differentiation, 23 as well as mass transport of biofactors and nutrients throughout the scaffold. 19,24,25 In bioseparation, control over the shape anisotropy of hydrogel pores may enhance the selectivity of the filtration of biological species and/or minimize the pressure drop across the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…CNTs are interesting materials because of their unique mechanical and electrical properties [62]. They may be used as scaffolds for cardiac or neural tissue [63]. MacDonald et al showed that incorporation of SWCNT into a collagen hydrogel embedded with human dermal fibroblast cells led to a hydrogel with decreased gel compaction.…”
Section: Biohybrid Fibrin and Collagen Hydrogelsmentioning
confidence: 99%